Experimental study on ECC-based unreinforced shield tunnel segmental joints for future resilient infrastructure - Minjin Cai; Timon Rabczuk; Xiaoying Zhuang (Underground Space)
To advance resilient infrastructure, this study explores unreinforced shield tunnel segment technologies, a critical but under-researched area. It conducted experiments on ECC-based unreinforced segments (ECCUS), comparing them with ECC-based reinforced segments (ECCRS) and reinforced concrete segments (RCS), focusing on their mechanical properties, including material characteristics, segmental deflection, joint behavior, bolt strain, damage propagation, failure modes, joint toughness, and ductility. Key findings include: (1) ECCUS joints exhibited significantly enhanced bearing capacity, with ultimate strength 34% higher than RCS and 29% higher than ECCRS. In terms of initial cracking strength, ECCUS outperformed RCS by 200% and ECCRS by 34%. (2) The absence of reinforcement cages in ECCUS reduced stiffness but improved overall segment coordination and deformation, leading to deflections 100% greater than RCS and 85% than ECCRS. (3) ECCUS and ECCRS displayed numerous, fine cracks under 200 µm wide, while RCS showed fewer, wider cracks over 3 mm, leading to significant spalling. Cracks in ECCUS were densely distributed across shear and compression zones, in contrast to RCS and ECCRS where they concentrated on compression areas. (4) ECCUS joints exhibited remarkable toughness, with elastic phase toughness 13.47 times that of RCS and 1.91 times that of ECCRS. In the normal serviceability phase, the toughness of ECCUS was 12.17 times that of RCS and 2.53 times that of ECCRS. (5) Considering multi-scale mechanical effects, ECCUS joints amplified the material advantages of ECC over RC more than 11 times during the elastic stage. These findings offer valuable insights for future resilient infrastructure development based on unreinforced construction technologies.